Las representaciones de la muerte en la taberna de Émile Zola. O sobre las nuevas modalidades de morir en Occidente - Dubin, Mariano (Nómadas. Critical Journal of Social and Juridical Science, 2009)
The present article merges an analysis about Émile Zola´s La Taberna with changes regarding death that took place in Modernity. We consider that La Taberna explains several representations about death, as well as its progressive process of institutionalization. Before Modernity, death was a diagnosis of individuals themselves. Afterwards, a specialized discourse emerged, and was presented as the legitimate approach to explain what happens to the individuals.
Keywords: La taberna; Émile Zola; Representations about death; Modernity